Report on industrial attachment with ABB Transformers Pte Ltd Singapore - Tor, Roy Seng Teong. (2008)
The project entitled eUpgrading of Existing TXCADe and eNew Design Software for ESI Type Transformere were assigned to the writer during this period. Upon completion of these projects, a new software ESICAD 2000 is developed and the existing TXCAD 2000 is also upgraded.